OPTIMALISASI PENGGUNAAN SUPERPLASTICIZER MASTERGLENIUM ACE 8595 DALAM IMPLEMENTASI PEKERJAAN BETON - Mahendra Septa Kuswiantoro; Zendy Bima Mahardana; Ma’rifatul Mumayyizah; Alfina Iskindaria; Rifqi Sahrul Nurhuda; Farikhatul Mufaidah; Moch Risjad Aldiansyah (LPPM Universitas Abdurrab, 2024)
Technological advances in the construction world are growing rapidly, including the development of materials and construction methods. The use of superplasticizer additives in the manufacture of concrete can increase compressive strength and viscosity in achieving the workability of concrete cast work. Itis necessary to optimize the proportion of the use of superplasticizer additives to achieve the best workability. This study aims to determine the best workability in the use of concrete mixture superplasticizer admixture. The additive used is MasterGlenium ACE 8595 with a percentage of use of 0.25%, 0.28%, 0.31%, and 0.34%. The results revealed that the best workability was obtained in the addition of admixture of 0.31% of the weight of cement with a slump value of 14 cm and a compressive strength value of 17.35 Mpa which indicates that concrete is suitable for use in non-structural elements such as cyclope, pavement and masonry bare concrete. Through these results, it is hoped that it can be used as a reference to find the best workability from the use of MasterGlenium ACE 8595 superplasticizer for the implementation of appropriate construction.